Subarray 4×4 untuk Antena MIMO 5G dengan Elemen yang Menerapkan Teknik Parasitic - Fitri Amillia; Eko Setijadi; Gamantyo Hendrantoro (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
Multiple-input multiple-output (MIMO) is a wireless communication system using multiple antennas on the transmitting and receiving sides. This system can improve the quality of wireless communication on 5G technology networks. The advantages of 5G include higher data rates and lower delays. The 5G network in Indonesia uses an intermediate frequency working in the 3.5 GHz frequency band. Antenna is an important device in a wireless network MIMO system. Therefore, this study proposes a single element design using parasitic techniques to widen the bandwidth to meet the needs of MIMO antennas and design a 4×4 subarray antenna for 5G MIMO. The method used began with determining the target antenna specifications, then designing a single element with a parasitic patch. The use of parasitic patches techniques on antenna elements aims to widen the bandwidth to meet target specifications. The resonant frequency of the microstrip antenna was affected by the increase in the number of parasitic patches. The number of resonant frequencies that arise resulted in a broad bandwidth. Then, the single elements with parasitic patches were arranged into a 4x4 subarray. All elements were arranged on the same substrate with a spacing between elements from one feed point to another was 64.28 mm or 0.75λ. The subarray design met the target antenna specifications if the subarray elements have a fractional bandwidth of more than 20% and mutual coupling of less than -20 dB. The material used in antenna design and fabrication was FR-4 (epoxy) substrate with a dielectric constant (ε_r) of 4.3 and a substrate thickness (h) of 1.6 mm. The results showed a bandwidth of 735 MHz or a fractional bandwidth of 20.35%, return loss of -14.65 dB, mutual coupling of -30.05 dB, and gain of 16.86 dB. Thus, the designed 4x4 subarray for MIMO antenna meets the desired specifications.